Influence of the process parameters on the mechanical properties of engineering biocomposites using a twin-screw extruder. (April 2016) - Feldmann, M.; Heim, H.-P.; Zarges, J.-C.
Abstract: The utilization of bio-based engineering polymers as a matrix material for cellulosic fiber reinforced composites has become an important focus in materials research. This is due to a rising demand for sustainable materials from renewable resources. In addition to this aspect, the bio-based materials provide an advantage for lightweight applications with their lower density. In this investigation, the completely bio-based polyamide 10.10, with a melting point above 200 °C, was used as a polymer matrix. Chopped man-made cellulose fibers (Cordenka CR-Type) were investigated as reinforcement for use in injection molded applications. A co-rotating twin-screw extruder with a screw-diameter of 18 mm was used for compounding. It was verified that reinforcing polyamide 10.10 with 20 wt% and 30 wt% cellulosic fibers is possible, resulting in an increase of impact and tensile properties. Furthermore, it was shown that the temperatures and screw-configurations of the twin-screw extruder only result in different fiber length distributions but in minor differences of the morphological structure and mechanical properties of PA 10.10 with 20 wt% fibers. Compounds with 30 wt% cellulose fibers show significant higher impact properties that those with 30 wt% glass fibers.